Tularemia treatment: experimental and clinical data - Maurin, Max; Pondérand, Léa; Hennebique, Aurélie; Pelloux, Isabelle; Boisset, Sandrine; Caspar, Yvan (Frontiers in Microbiology, 2024)
Tularemia is a zoonosis caused by the Gram negative, facultative intracellular bacterium Francisella tularensis. This disease has multiple clinical presentations according to the route of infection, the virulence of the infecting bacterial strain, and the underlying medical condition of infected persons. Systemic infections (e.g., pneumonic and typhoidal form) and complications are rare but may be life threatening. Most people suffer from local infection (e.g., skin ulcer, conjunctivitis, or pharyngitis) with regional lymphadenopathy, which evolve to suppuration in about 30% of patients and a chronic course of infection. Current treatment recommendations have been established to manage acute infections in the context of a biological threat and do not consider the great variability of clinical situations. This review summarizes literature data on antibiotic efficacy against F. tularensis in vitro, in animal models, and in humans. Empirical treatment with beta-lactams, most macrolides, or anti-tuberculosis agents is usually ineffective. The aminoglycosides gentamicin and streptomycin remain the gold standard for severe infections, and the fluoroquinolones and doxycycline for infections of mild severity, although current data indicate the former are usually more effective. However, the antibiotic treatments reported in the literature are highly variable in their composition and duration depending on the clinical manifestations, the age and health status of the patient, the presence of complications, and the evolution of the disease. Many patients received several antibiotics in combination or successively. Whatever the antibiotic treatment administered, variable but high rates of treatment failures and relapses are still observed, especially in patients treated more then 2-3 weeks after disease onset. In these patients, surgical treatment is often necessary for cure, including drainage or removal of suppurative lymph nodes or other infectious foci. It is currently difficult to establish therapeutic recommendations, particularly due to lack of comparative randomized studies. However, we have attempted to summarize current knowledge through proposals for improving tularemia treatment which will have to be discussed by a group of experts. A major factor in improving the prognosis of patients with tularemia is the early administration of appropriate treatment, which requires better medical knowledge and diagnostic strategy of this disease.